2013
DOI: 10.1177/1362361312472261
|View full text |Cite
|
Sign up to set email alerts
|

Family-focused autism spectrum disorder research: A review of the utility of family systems approaches

Abstract: A family member with an autism spectrum disorder presents pervasive and bidirectional influences on the entire family system, suggesting a need for family-focused autism spectrum disorder research. While there has been increasing interest in this research area, family-focused autism spectrum disorder research can still be considered relatively recent, and there are limitations to the existing literature. The purpose of this article is to provide theoretical and methodological directions for future family-focus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
125
1
9

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(138 citation statements)
references
References 74 publications
3
125
1
9
Order By: Relevance
“…In the present study, interactions in the family and the role of parents in enhancing children’s resilience were significant because children’s behaviour and learning are shaped by the family to a large extent. Other researchers have recognized the role of family in helping adolescents to adapt to tensions or unpredictable problems during adolescence (Cridland, Jones, Magee, & Caputi, 2014; Tatnell, Kelada, Hasking, & Martin, 2014). …”
Section: Discussionmentioning
confidence: 99%
“…In the present study, interactions in the family and the role of parents in enhancing children’s resilience were significant because children’s behaviour and learning are shaped by the family to a large extent. Other researchers have recognized the role of family in helping adolescents to adapt to tensions or unpredictable problems during adolescence (Cridland, Jones, Magee, & Caputi, 2014; Tatnell, Kelada, Hasking, & Martin, 2014). …”
Section: Discussionmentioning
confidence: 99%
“…The current findings suggests that such a comprehensive approach, in comparison to individual attention on family resources or coping strategies, may improve parental outcomes for families of children with ASD. In doing so, support services and intervention programs aimed at parents of children with ASD, of all ages, should attempt to work with the family (Cridland et al 2014) to assess and improve levels of FSOC within family members (i.e., mothers, fathers, siblings), emphasising these three domains of family life.…”
Section: Clinical Relevancementioning
confidence: 99%
“…The important role of parents in the child's development and intervention processes has been pointed out as essential by studies conducted in the last few years. However a literature review indicated that the number of studies about parents' participation is smaller than was expected (1,7,8) . There is also a lack of scientific publications based on results of academic research, which limits the outreach of the knowledge generated by recent research in the field (9) .…”
Section: Introductionmentioning
confidence: 92%